Heterogeneous Internal Financial Drivers of Operating Cash Flow: Evidence from Quantile Regression in an Emerging Market - Ali, Muhammad Aamir; Aamir, Nazish; Sattar, Ali Raza (Buhalterinės apskaitos teorija ir praktika, 2026)
This study aims to examine the determinants of operating cash flow (cash flow from operating activities, OCF) in dividend-paying firms in Pakistan. Using firm-level data and applying quantile regression alongside ordinary least squares (OLS), the analysis captures variations across the conditional distribution of OCF beyond mean-based estimates. The results indicate that total assets are negatively associated with OCF across most quantiles, suggesting lower efficiency in cash generation among larger firms. In contrast, sales and fixed assets exhibit consistently positive relationships, highlighting their importance for operational performance. Risk shows a positive association, particularly at higher quantiles, indicating stronger cash generation among higher-risk firms. Dividend payout is significant only at the upper quantile, implying a limited role relative to operational factors. Firm age is significant at lower and median quantiles but not at higher levels. Overall, the findings emphasize the role of operational scale, asset utilization, and risk in shaping OCF, with implications for financial decision-making in emerging markets.